Pembangunan aplikasi panduan solat untuk platform android (Muslim Solah) - Azmi, Shahdatunnaim (2013)
Muslim Solah application developed to help provide guidance on how to properly set up compulsory Solah and Solah who cashed in imperfect condition as in sitting and lying down. Muslim Solah development process taking into account the characteristics found in Solah applications that have been around the market. Detailed studies have been done to produce a compact application informative and user friendly. Solah application development projects important to Muslims as it is still less developed form of Islamic applications developed while growing consumer demand in particular for applications that provide guidance on how to establish Solah. As it viewed from the aspect of competition, Muslim Solah highlighting much unique knowledge on Solah differs from existing applications in market. Among the peculiarities shown includes a guide to perform Solah in a variety of situations, such as standing, sitting and lying down. In addition, the application also highlights the critical mistakes in regular movements while performing Solah. With this, users can learn how to properly set up Solah and reduce the frequent offenses committed while performing Solah.